Fuzzy method for analysing uncertainty in the sustainable design of concrete structures. Issue 7 (2nd October 2016) - del Caño, Alfredo; Pilar de la Cruz, M.; Gómez, Diego; Pérez, Miguel
Abstract: The model presented here is based on fuzzy arithmetic techniques and the MIVES method, which is based, in turn, on requirement trees, value analysis and the Analytic Hierarchy Process. Even though it encompasses the approach for assessing sustainability adopted by the Spanish Structural Concrete Code (EHE), the model can also be applied to concrete structures designed according to other structural codes. The EHE model serves to estimate the Structure's Contribution to Sustainability Index ( ICES ) and constitutes the first sustainability model included in a structural code. The ICES crisp model is inadequate in terms of managing the structural sustainability objective of medium and high uncertainty projects. In such cases, a method not only has to assess the potential sustainability index at the end of the project, but also the degree of uncertainty affecting compliance with the sustainability objective laid down by the client or promoter. The paper compares this model with a Monte Carlo simulation method conceived for the same purpose. The fuzzy method could be a better solution in specific cases of limited time or budget for creating the model.